(3OjhGf GdYTGQjs - (3MSjf Hf Ydj Hf MSf Hf eMeO GdYTGQj GdHZOGOj GdTGaYj,J (B1194 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3cfJ aj CHGf GdTHGH eTZhakG HVGYI GdCOH, ebJfUkG ef dWGFa GdYQH Cef JPcQ LjQGf HPj Sde fMQJ bdHc Hjf hGdYde s
(3BNQgG (B:s
(3jG Gdgi Ud Ydi bHQ Wg hYdi Bdg hcd Jbi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B28s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B518 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B156 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbj HHZOGO (B(317) s
Keywords: (3GdCOHs